Learning for Climate Change Adaptation among Selected Communities of Lusaka Province in Zambia - Manoah Muchanga (Environmental Association of Southern Africa, 2013)
This research was aimed at surveying perceptions of climate change and educational themes that would be contextually relevant for climate change adaptation. It locates within the United Nations' Educational, Scientific and Cultural Organization's (UNESCO's) Balaclava recommendations on Climate Change Education for Sustainable Development (2013). Uncertainty as to how residents of selected households understood the causes and effects of climate change as well as the content structure of learning for climate change adaptation constituted the problem. Using social constructivism, hermeneutics, survey design, semistructured interviews and constant comparative analysis, the article shows that the challenges of climate change are comprehended in diverse ways. It also shows that drawing knowledge from diverse sources or cross-disciplines can evoke behavioural and social change that is critical in order to nurture best thinking and practices regarding adaptation.